19. POLITIK HUMANITARIANISME: KETIADAAN INTERVENSI KEMANUSIAAN DALAM PERANG SAUDARA SRI LANKA 2001-2009 - Adinda Kinanti Prameswari; Reni Windiani; Mohamad Rosyidin (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2017)
The ethnic disrimination done by Sri Lankan government had made the outbreak of ethnicconflict in Sri Lanka for more than 26 years between government of Sri Lanka against LTTErebels. Although many crimes such as crime against humanity and war crimes occured, therewere no action taken by international community to intervene the situation. This researchaimed to analyse the absence of humanitarian intervention in Sri Lanka to end conflict.Realism theory of International Relations is used to be research framework, the researchargues that the absence of humanitarian intervention happened due to there're no nationalinterest taken by foreign states to enter Sri Lanka. Using secondary data collection methodthrough study library. Geopolitically, Sri Lanka is a disaster phrone land and also notstrategic country. Economically, Sri Lanka doesn't have valuable natural resources such asgas and oil which are looked by the West.